Methane emission and milk production of dairy cows grazing pastures rich in legumes or rich in grasses in Uruguay - Dini, Yoana (2012)
Understanding the impact of changing pasture composition on reducing emissions of GHGs in dairy grazing systems is an important issue to mitigate climate change. The aim of this study was to estimate daily CH4 emissions of dairy cows grazing two mixed pastures with contrasting composition of grasses and legumes: L pasture with 60% legumes on Dry Matter (DM) basis and G pasture with 75% grasses on DM basis. Milk production and CH4 emissions were compared over two periods of two weeks during spring using eight lactating Holstein cows in a 2 × 2 Latin square design. Herbage organic matter intake (HOMI) was estimated by chromic oxide dilution and herbage organic matter digestibility (OMD) was estimated by faecal index. Methane emission was estimated by using the sulfur hexafluoride (SF6) tracer technique adapted to collect breath samples over 5-day periods. OMD (0.71) and HOMI (15.7 kg OM) were not affected by pasture composition. Milk production (20.3 kg/d), milk fat yield (742 g/d) and milk protein yield (667 g/d) were similar for both pastures. This may be explained by the high herbage allowance (30 kg DM above 5 cm/cow) which allowed the cows to graze selectively, in particular in grass sward. Similarly, methane emission expressed as absolute value (368 g/d or 516 L/d) or expressed as methane yield (6.6% of Gross Energy Intake (GEI)) was not affected by treatments. In conclusion, at high herbage allowance, the quality of the diet selected by grazing cows did not differ between pastures rich in legumes or rich in grasses, and therefore there was no effect on milk or methane production.